Literasi Baitul Maqdis dalam Membina Kesadaran Keagamaan Umat di Era Pendidikan Islam Kontemporer - Eka Susanti; Nuril Huda (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
One of the conceptual approaches in Islamic education that is rarely used as a foundation for strengthening religious awareness is Baitul Maqdis-based literacy education. This literacy not only relates to understanding history and the Palestinian issue, but also encompasses theological and spiritual awareness, as well as the Islamic civilization rooted in the values of tawhid, brotherhood, and social justice. This study employs a descriptive qualitative method with a descriptive-analytical approach, supported by a literature review of relevant scholarly works. The findings indicate that Baitul Maqdis literacy has significant potential in cultivating religious awareness among Muslims. Through the integration of Baitul Maqdis literacy into contemporary Islamic education, it is expected that a generation with maqdisiyyah awareness will emergenamely, Muslim learners with strong faith, critical thinking skills, historical consciousness, and a commitment to the advancement of global Islamic civilization.